PENGARUH PENGAWASAN DAN KOORDINASI TERHADAP KINERJA PEGAWAI PADA SEKSI PENGAWASAN TATA RUANG BANGUNAN DINAS CIPTA KARYA BINA KONSTRUKSI DAN TATA RUANG KOTA BANDUNG - Lita Juliati; Fitra Nurhakim; Arneta Maharani (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
The less-than-optimal performance of employes in the Spatial Planning and Building Supervision Section of the Bandung City Public Works, Construction and Spatial Planning Department is a major concern, characterized by delays in task completion and poor discipline. This phenomenon is believed to be influenced by the ineffective supervision and coordination functions of the leadership. The purpose of this study is to examine how employee performance is impacted by coordination and supervision. Data was gathered quantitatively by giving questionnaires to 92 respondents who were chosen at random. Multiple linear regression, the F-test, and the t-test were used for data analysis. The study's findings indicate that: (1) With a computed t-value of 5.242, supervision (X1) has a positive and substantial impact on employee performance. (2) With a computed t-value of 4.332, coordination (X2) has a positive and significant impact on employee performance. (3) With a computed F-value of 66.876, supervision and coordination simultaneously have a significant impact on employee performance. These two independent factors account for 60% of employee performance variables, with supervision being the most important element, according to the coefficient of determination (R²).. Increased effectiveness of supervision and coordination has been proven to significantly improve employe performance. Keywords: Supervision, Coordination, Employee Performance, Responsibility, Leadership.